Role of Students’ Feedback to Faculty Members for Institutional Quality Support System in Community Colleges in Baghmati Province - Gautam, Tara Prasad; Mishra, Anjay Kumar; V T, Shailashri (NPRC Journal of Multidisciplinary Research, 2025)
Student feedback is increasingly recognized as a pivotal component of quality assurance in higher education. This study examines how students' feedback to professors enables five community colleges in Bagmati Province, Nepal assist institutional excellence. The study employed a mixed-methods strategy combining a survey of 250 students with in-depth interviews and focus groups. Although highlighting certain areas for improvement such as course organization and teaching methods, statistical data reveal that students generally rated professors favorably in categories including subject expertise and communication skills. Qualitative theme analysis highlighted students' need for more participatory instruction, timely course completion, and unambiguous reactions to their comments. Therefore underlining key factors of perceived teaching quality, effective communication and general satisfaction revealed a positive link (r = 0.82). Building on these findings, we propose a "Feedback-to-Action" approach that closes the loop from feedback collecting to faculty development and policy improvement. Consistent with world best practices in continuous quality improvement, the framework emphasizes systematic data analysis, faculty involvement, action planning, and follow-up. By demonstrating that systematic use of student feedback can enhance internal quality support systems, the study contributes to the little body of work on student voice in Nepal's higher education quality assurance. Policy recommendations advocate for integrating students in quality assurance committees, incorporating feedback results into teacher development initiatives, and institutionalizing regular feedback mechanisms. Active utilization of student input, according to this study, can propel pedagogical growth, greater student happiness, and a culture of accountability and excellence in community college education.